(untitled) (Ustozlar uchun, 2026)
Areal linguistics studies the territorial distribution of linguistic features – across one language or dialect, as well as across several related or unrelated languages – through the analysis of isoglosses. Using the methods of linguistic geography, it collects data on language features, while linguistic geography, in conjunction with cartography, focuses on mapping these features based on the collected material. This article describes and classifies the principles for creating a linguistic atlas, one of the main research objects of areal linguistics. In particular, it examines the principles for developing an atlas that summarizes the grammatical features of the Uzbek language.